Multidimentsional leadership orientations and lecturers' work commitment:the mediation of leadership effectiveness among Malaysian Poleytechnic Heads of Department - Mohammed Sani Ibrahim,; Saedah Siraj,; Siti Junaidah Mohd Mujir, (Penerbit Universiti Kebangsaan Malaysia, 2012)
The purpose of this study was to determine if the perceived leadership effectiveness of heads of departments in Malaysian polytechnics mediates the relationship between their leadership orientation and the work commitment of lecturers. Leadership orientation was defined in its structural, human resource, political, cultural, and educational dimensions, based on Bolman and Deal’s leadership frame and Sergiovanni’s leadership model. A total of 841 lecturers and 76 department heads from Malaysian polytechnics participated in this study. Hierarchical Linear Modelling was used to determine the department heads’ perception of the impact of their leadership effectiveness on the relationship between their leadership orientation and lecturers’ work commitment. The study proved that the heads of department practised multidimensional leadership, and that the effect of this on lecturers’ work commitment was mediated by lecturers’ perception of department heads’ leadership effectiveness.